Investigating the Tribological Performance of Natural Rubber Additives in Palm Oil-Based Lubricants - Aji, Ahmad Frantoni; Alfian, Devia Gahana Cindi; Prasetyo, Tri Wahyu; Firjatullah, Ahmad Labib; Sufra, Rifqi; Pujiyulianto, Eko; Silitonga, Dicky Januarizky; Auriyani, Wika Atro; Yusupandi, Fauzi (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2024)
Human dependence on mineral-based energy sources poses challenges related to toxicity, depletion, degradation, and environmental hazards. An appropriate replacement for mineral-based lubricants has yet to be realized; one available option for humans is alternative, renewable, environmentally friendly, and biodegradable energy sources. Lubricants play an important role in product processing, transportation, agriculture, and other key sectors in industrial development. This study was conducted to explore the potential use of palm oil as the main ingredient with the addition of rubber as an additive. The method of making the lubricant involved mixing 3%, 5%, and 7% rubber latex with sonicated palm oil using UAE. Next, wear testing was performed using a tribometer based on the ball-on-disc principle, utilizing a modified bench-top drill machine. The testing was carried out at room temperature, maintaining a constant load of 8.83 N and a rotational speed of 180 rpm for 5 minutes per sample. Microscopic analysis of the wear scars on the plate samples showed different wear patterns and characteristics for each lubricant, with measurements taken at various positions for accuracy. The results indicated that the lubricant with a 5% rubber mixture was the best, with a wear width of 535.9126 µm, compared to the commercial lubricant (SAE 15W 40) which had a wear width of 539.906 µm. This research demonstrates the potential use of a palm oil and rubber mixture as a more environmentally friendly lubricant alternative.